Evidence of Hearing Loss and Unrelated Toxoplasmosis in a Free-Ranging Harbour Porpoise (Phocoena phocoena) - Maria Morell (MDPI AG, 2021)
Evidence of hearing impairment was identified in a harbour porpoise (Phocoena phocoena) on the basis of scanning electron microscopy. In addition, based on histopathology and immunohistochemistry, there were signs of unrelated cerebral toxoplasmosis. The six-year old individual live stranded on the Dutch coast at Domburg in 2016 and died a few hours later. The most significant gross lesion was multifocal necrosis and haemorrhage of the cerebrum. Histopathology of the brain revealed extensive necrosis and haemorrhage in the cerebrum with multifocal accumulations of degenerated neutrophils, lymphocytes and macrophages, and perivascular lymphocytic cuffing. The diagnosis of cerebral toxoplasmosis was confirmed by positive staining of protozoa with anti-Toxoplasma gondii antibodies. Tachyzoites were not observed histologically in any of the examined tissues. Ultrastructural evaluation of the inner ear revealed evidence of scattered loss of outer hair cells in a 290 µm long segment of the apical turn of the cochlea, and in a focal region of ~ 1.5 mm from the apex of the cochlea, which was compatible with noise-induced hearing loss. This is the first case of concurrent presumptive noise-induced hearing loss and toxoplasmosis in a free-ranging harbour porpoise from the North Sea.